Analisa Komparasi Perangkat Speech Recognizing dan Potensinya dalam Membantu Proses Pembelajaan Difabel Rungu Guna Terciptanya Kampus Inklusif Di Era 4.0 - Chandra Halim; Febri Satria (Risenologi, 2020)
The lack of facilities and infrastructures for students with special needs will hamper the learning process. In fact, this has been explained in the definition of inclusive education which is to accommodate students with special needs to comprehend the material in the class. The fact is that there are only public facilities such as the guiding block for the blind, and some interpreters in the class to explain the material. This situation is exacerbated by the limitations of an interpreter to explain scientific terms. Therefore, we need a technology that can help deaf people to comprehend the material in the classroom directly. The technology is speech recognizing device. This device enables to process input signals in the form of sound and is converted into text. This technology enables deaf people to comprehend material in the classroom without an interpreter. The research method is inferential statistics and observations. Observations were made by measuring 26 respondents speaking speed to obtain data using 3 different applications namely Speech Notes, Voice Notebooks, Speech to Text. Afterthat, the words obtained in the application are compared with the actual text to see the accuracy of each application. By using inferential statistics, the correlation test values obtained in the application of Voice Notebooks, Speech Notes, Speech to Text are 0.386,0.351, and 0.152, respectively. By using 5% significance level, we found that the most accurate speech recognizing application is Voice Notebook. Due to Voice Notebook application, we can support the special students in learning process in the class.